Professional blogging for dummies - Getgood, Susan; Safari eBooks (Hoboken, N.J. : Wiley, 2010)
"Anyone who blogs knows that it is a fun, creative way for sharing thoughts and opinions. Now imagine making money from that hobby! This practical, how-to guide shows you how you can get serious about using your blog and implement advertising, sponsorship, partnerships, and affiliate marketing options to turn your hobby into extra income, or even a full-time career. Helpful examples and featured articles with topic experts and bloggers who have built successful business demonstrate how to promote your business or build a blog-based business"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Blogs; Internet marketing; Marketing -- Blogs; Social media -- Economic aspects; Online social networks -- Economic aspects; Electronic books